Incorporation of Sunflower Oil and d-alpha-tocopherol Effect on Mechanical Properties and Permeability of Corn Starch Composite Edible Film - Pramono Putro Utomo; Farid Salahudin (Balai Riset dan Standardisasi Industri Pontianak, 2015)
Corn starch-based films are inherently brittle and lack the necessary mechanical integrity for conventional packaging. However, the incorporation of additives can potentially improve the mechanical properties and processability of starch films. In this work sunflower oil (SO) and vitamin E (d-alpha-tocopherol) at three levels each (0.05%, 0.1% and 0.15% (w/vtotal)) and (0.18%, 0.36% and 0.54% (w/vtotal)) were incorporated into corn starch films using a solution casting method to improve the mechanical and water vapour transmission rate (WVTR) properties. The addition of SO and vitamin E increased elongation at break of starch-based film while decreased tensile strength and WVTR of starch-based film. The best edible film obtained on addition of sunflower oil concentration of 0.15% and 0.54%, vitamin E with a value of 0.121 mm thickness, tensile strength of 65.38 kg/cm2, elongation at break 14.17% and WVTR 1144 g/m2 24 hours.